Insight into physics‐based RRAM models – review. Issue 7 (23rd May 2019) - Lekshmi Jagath, Arya; Hock Leong, Chee; Kumar, T. Nandha; Almurib, HaiderA.F.
Abstract : This article presents a review of physical, analytical, and compact models for oxide‐based RRAM devices. An analysis of how the electrical, physical, and thermal parameters affect resistive switching and the different current conduction mechanisms that exist in the models is performed. Two different physical mechanisms that drive resistive switching; drift diffusion and redox which are widely adopted in models are studied. As for the current conduction mechanisms adopted in the models, Schottky and generalised hopping mechanisms are investigated. It is shown that resistive switching is strongly influenced by the electric field and temperature, while the current conduction is weakly dependent on the temperature. The resistive switching and current conduction mechanisms in RRAMs are highly dependent on the geometry of the conductive filament (CF). 2D and 3D models which incorporate the rupture/formation of the CF together with the variation of the filament radius present accurate resistive switching behaviour.